PENGARUH KONSELING GIZI DENGAN MEDIA BOOKLET TERHADAP KONSUMSI SAYUR BUAH DAN FAST FOOD PADA REMAJA OBESITAS - Neldawati Ningrum; Ria Ambarwati; Enik Sulistyowati (JURNAL RISET GIZI, 2019)
Background: Several factors cause obesity in adolescence are the lack of consumption of vegetables, fruits and excessive consumption of fast food. Nutrition counseling about benefits of vegetables, fruits and the impact of fast food on obesity is an effort that would be increase consumption of vegetables, fruits and reduce consumption of fast food.Objective: To determine the effect of counseling with booklet media on consumption of vegetables, fruits and fast food in obese adolescents at SMP N 40 Semarang.Method: The type of research is a true experiment with randomized pre and post test control group design. The research subjects consisted of 15 intervention samples who took nutrition counseling treatment with booklet media and 15 control samples were only given booklet media without nutritional counseling. The data was analysed by Independent T Test and Mann Whitney.Results: Nutrition counseling with booklet increased vegetable consumption (0,37 portion) and decreased fast food consumption (1,09 portion) but the result were not significant in the statistical test (p 0.05). However, nutrition counseling with booklet significantly (p 0.05) increased fruit consumption (0,63 portion).Conclusion: Nutrition counseling with booklet increased consumption of vegetables and fruits, and also reduce consumption of fast food.